DIFERENSIASI DAN TINGKAT PEMAHAMAN PRODUK, SERTA KUALITAS SUMBER DAYA MANUSIA ATAS KEPUTUSAN NASABAH PERBANKAN SYARIAH - Khasanah, Uswatun; Muamar, Afif (Ekonomi Islam, 2019)
The greater growth of the banking industry creates increasingly fierce competition between the sharia banking industry so that it will make consumers have many alternative choices before deciding which bank to aim for sharia banking transactions. This study aims to reveal the level of understanding of the quality of human resources of customers to customer decisions, the perception of product differentiation of customer decisions. This study uses qualitative research, data collected by interview, observation, documentation and then analyzed using a descriptive analysis method. The results of the study prove the customer's perception of product differentiation, the level of product understanding, and the quality of human resources have a positive influence on customer decisions in Islamic Banking. This means that according to consumers the three components are considered important when using services in Islamic Banking. Keywords: Products, Quality of Human Resources, Customer Decisions